EVALUATION OF SURFACTANT WITH THIN FILM SPREADING MECHANISM FOR EOR IMPLEMENTATION - Sugihardjo Sugihardjo (Scientific Contributions Oil and Gas, 2014)
Wettability plays an important role of two phase Àuids Àow in porous media. The displacement efficiency of oil by injected Àuid is also dictated by wettability characteristic of reservoir rocks. This papers contents a highlight of the reservoir wettability modification by injecting TFSA (Thin Film Spreading Agent) surfactant for EOR applications through a laboratory study . TFSA used in this study is called Coconut Ethanolamide with a HLB (Hydrophilic-Lipophilic Balance) level around 13 to 15 which is very suitable for TFSA purposes. Several laboratory evaluations have been done to screen this surfactant with the aim of getting the best properties that fulfill the criteria for EOR chemical injection. Then TFSA solution tests have been carried out including compatibility, thermal stability, phase behavior, and filtration test. The results suggest that all measured parameters are suitable for chemical injection. Others parameters measuring rock Àuid interactions for instance: adsorption, wettability, imbibition, relative permeability, and core Àood experiments has been done to find the quantitative numbers for screening this surfactant. All experiment results categorize as moderate levels for passing the screening criteria for chemical injection except for the adsorption which is excellent. Even though the results of laboratory tests show this TFSA is valid for chemical injection, improvement by adding some chemicals is still suggested to find a better TFSA formula.